Integrity assessment of clad pipe girth welds - Carlucci, A.; BONORA, Nicola; RUGGIERO, Andrew; IANNITTI, Gianluca; TESTA, Gabriel (Volume 6A: Pipeline and Riser Technology, 2014)
Current design standards and codes do not provide specific guidance how to perform engineering criticality assessment with bi-metallic girth weld in lined or clad pipe. Recently, Bonora et al. (Proc. ASME 2013 32nd OMAE conf.) proposed the equivalent material method (EMM) which allows one still to use current design assessment routes. The method consists in considering instead of three materials in the weld joint, a single "equivalent" material with a flow curve defined as the interpolated lower bound of the three weld joint material flow curves. In this work, the applicability of the EMM was verified considering the effect associated with inner pressure loading and weld residual stresses. To this purpose, two flaw geometry configurations have been investigated. Particular relevance was given to the multi-pass weld process simulation. Numerical results indicate that the EMM always provides conservative results in terms of applied J with respect to those estimated considering the effective multi-materials configuration in the weld joint. Copyright © 2014 by ASME.